Spectral light sensitivity and anomalous quotient in anomalous trichromats with protanomaly and deutanomaly (Ukrainian Journal of Ophthalmology, 2026)
Background. An ability to precisely distinguish red and green colors is crucial for many professions, which has conditioned the importance of color vision diagnostics and its application in vocational selection.Purpose: to determine the acuity of color perception, using anomaloscope data on spectral light sensitivity in threshold testing the main types of classes of cones, as well as the anomalous quotient in anomalous trichromats of various severity.Material and Methods. The study was performed in anomalous trichromats with emmetropic refraction and visual acuity of 1.0. A group of protanomalous trichromats: type C, 132 persons (264 eyes); type B, 138 persons (276 eyes); type A, 120 persons (240 eyes). A group of deutanomalous trichromats: type C, 366 persons (732 eyes); type B, 207 persons (414 eyes); type A, 30 persons (60 eyes). 77 normal trichromats without concomitant ocular and systemic diseases served as Control. The patients aged 16 to 33 years. The acuity of color perception was determined using an AN-59 anomaloscope with three tests: 1 (red), 2 (green), and 3 (blue) colors in a mode of graded color differences. Anomaly quotient (AQ) was also calculated. Results. The acuity of color perception according to anomaloscope color thresholds was highest and lowest in blue and red colors, respectively, in both normal and anomalous trichromats. Blue, green, and red color thresholds averaged 10.3 RUs, 15.3 RUs, and 17.1 RUs, respectively, in normal trichromats. The most expressed decrease in the acuity of color perception was in anomalous trichromats of type A, from 14% to 18.3%, while the least expressed decrease was in type C abnormality, from 3.9% to 9.7%, in all three colors. Spectral abnormality is characterized by the anomalous quotient (AQ). In protanomalous trichromats, AQ ranged from 0.34 to 0.52, with the decrease by 18.3 in the severe form: type C AQ =0.49±0.01 vs. type A AQ=0.40±0.03. In deutanomalous trichromats, AQ ranged from 2.63 to 3.56, with the increase by 10.7 in the severe form: type C AQ =2.8±0.08 vs. type A AQ=3.10±0.20.Conclusion. The acuity of color perception was determined in anomalous trichromats with various severity of color deficiency.
Keywords: anomalous trichromatism; color vision; anomaly quotient; anomaloscope